Individuals of older adults hospitalized with social isolation - Jercy Subyen Iglesias Toriza; Elaine Teresa Gutiérrez Pérez; Linet Pérez Jurajuria; Galia Yagnalis Delgado Pagán; Yara Díaz Ibáñez (Acta Médica del Centro)
Introduction: social isolation is a complex and multidimensional phenomenon that affects people's lives, promotes inequality and affects dignity and personal and social identity. Objective: to describe characteristics of hospitalized older adults with social isolation. Methods: a cross-sectional descriptive study was carried out at the “Arnaldo Milián Castro” Hospital during the period from 2017 to 2020. The population was 44 older adults with social isolation treated in the Geriatrics Service. Observation, interviews, documentary analysis of medical records and the social-gerontological evaluation instrument were used in data collection. The statistical analysis was descriptive and inferential. Results: of the total patients, 68.2% were men, around 50% were grouped in the age groups between 65 and 69 and 75 and 79 years, 72.7% had no previous institutionalization, 27.3% suffered depression and 13.6% anxiety, 72.7% did not complicate their health status and their recovery was slow and 68.2% of adults with children were recorded. Family emigration (22.7%), toxic habits (18.3%) and housing problems (13.6%) were identified as causes of isolation. Conclusions: the male sex and the age groups between 65 and 69 and 75 and 79 years predominated, there was an association between the male sex and institutionalization and the presence of complications and slow recovery of health status. Family emigration, toxic habits and disabling diseases were the causes of isolation and depression was the most frequent consequence in both sexes.